Posttraumatic Stress Disorder-Related Differences in Neural Connectivity Among Female Trauma Survivors - Natalie C. Noble; Mohammad S.E. Sendi; Julia B. Merker; Samantha R. Linton; Theresa K. Webber; Russell T. Toll; Amit Etkin; Wei Wu; Kerry J. Ressler; Antonia V. Seligowski (Biological Psychiatry Global Open Science)
Background: Posttraumatic stress disorder (PTSD) is a debilitating condition that disproportionately impacts females. Prior research indicates that males with PTSD exhibit hypoconnectivity of frontal brain regions measured with resting electroencephalography (EEG). In the current study, we examined functional connectivity among females with PTSD and trauma-exposed control females, as well as the impact of sex hormones. Methods: Participants included 61 females (mean age = 31.41 years, SD = 8.64) who endorsed criterion A trauma exposure. Resting-state EEG data were recorded for 5 minutes in the eyes-open position. Using a linear mixed-effects model, functional connectivity of the theta band (4–7 Hz) served as the response variable. Results: Compared with the control group, the PTSD group showed hyperconnectivity between visual brain regions and the rest of the cerebral cortex (false discovery rate–corrected p [pFDR] < .05). Additionally, participants with PTSD demonstrated enhanced connectivity between the default mode network and frontoparietal control network compared with control participants (pFDR < .05), as well as increased connectivity between the ventral attention network and the rest of the cerebral cortex (pFDR < .05). Estradiol was associated with higher connectivity, while progesterone was associated with lower connectivity, but these associations did not survive correction. Conclusions: The results are consistent with prior research indicating that PTSD is associated with altered connectivity in visual brain regions, which may reflect disrupted visual processing related to reexperiencing symptoms (e.g., intrusive memories). Our findings provide additional support for the relevance of the theta frequency range in PTSD given its role in fear learning and regulation processes.